Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.orglett.7b00865
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption and Electron Paramagnetic Resonance Guided Discovery of the Cu-Catalyzed Synthesis of Multiaryl-Substituted Furans from Aryl Styrene and Ketones Using DMSO as the Oxidant

Abstract: The first example of DMSO serving not only as a solvent but also as an oxidant to promote the oxidation of Cu(I) to Cu(II) has been demonstrated. X-ray absorption and electron paramagnetic resonance evidence revealed a single-electron redox process where DMSO could oxidize Cu(I) to Cu(II). The novel discovery guided the rational design of copper-catalyzed oxidative cyclization of aryl ketones with styrenes to furans, providing a new method for the synthesis of multiaryl-substituted furans from cheap and readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 46 publications
(10 reference statements)
1
16
0
Order By: Relevance
“…under the deactivating, oxidative nature of the DMSO solvent. The above experiments with a model fluorogenic "click" reaction and different reaction media provide solid support that the intra-chain distribution of catalytic sites has an important effect on the catalytic activity of "clickase" SCNPs, especially in solvents with significant oxidative nature like DMSO [67].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…under the deactivating, oxidative nature of the DMSO solvent. The above experiments with a model fluorogenic "click" reaction and different reaction media provide solid support that the intra-chain distribution of catalytic sites has an important effect on the catalytic activity of "clickase" SCNPs, especially in solvents with significant oxidative nature like DMSO [67].…”
Section: Discussionmentioning
confidence: 69%
“…Remarkably, the difference in catalytic activity observed (Ck-SCNPs2 > Ck-SCNPs1 > CuSO4) was more notorious in DMSO than in aqueous THF. The slower reaction rate in DMSO can be attributed -to a large extent-to the oxidant power of this solvent [67] that oxidizes a certain amount of Cu(I) ions generated by NaAsc to Cu(II) ions, the latter being inactive for the "click" reaction. Interestingly enough, the presence of cluster of Cu ions in the case of Ck-SCNPs2 was found beneficial for improving the stability and effectiveness of the "clickase" SCNPs…”
Section: Resultsmentioning
confidence: 99%
“…[147] 2,3-Diphenyl-4H-indeno[1,2-b]furan 199 was prepared by the oxidative coupling of deoxybenzoin and indene promoted by CuCl 2 ; the proposed reaction mechanism included the formation of an α-keto radical followed by the addition of this radical to indene (Scheme 30). [148]…”
Section: H-indeno[12-b]furanmentioning
confidence: 99%
“…Preparation of 2,3-diphenyl-4H-indeno[1,2-b]furan and proposed reaction mechanism. [148] Scheme 31. Synthesis of 4H-indeno[1,2-b]thiophene 201.…”
Section: H-indeno[12-b]thiophenementioning
confidence: 99%
“…Similarly in 2017, Lei and co-workers reported a facile CuCl 2 -catalyzed oxidative cyclization of aryl ketones and styrenes towards the synthesis of multisubstituted furan derivatives. 43 Interestingly, through X-ray absorption and electron paramagnetic studies they revealed that DMSO, besides serving as a solvent, plays the crucial role of an oxidant to promote the oxidation of Cu(I) to Cu(II).…”
Section: Short Review Syn Thesismentioning
confidence: 99%